Orthopedic Treatment of Diseases and Fractures in Elderly - Testa, Gianluca (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Elderly frailty represents the poor resolution of homeostasis following stress and an increased risk of adverse outcomes, including falls, delirium and disability. This reprint is focused on the diagnosis and treatment of fractures and orthopedic diseases among elderly people. In particular, this concerns medical, orthopaedics and rehabilitative factors. This reprint includes original articles, narrative or systematic reviews and meta-analysis, aiming to provide readers with the correct approach to these pathologies.